Uso de clorexidina 2% gel e escovação na higiene bucal de pacientes sob ventilação mecânica: efeitos na pneumonia associada a ventilador - Meinberg, Maria Cristina de Avila (2013)
Introduction: Nosocomial pneumonias determine a significant increase length of Stay, in hospital costs and mortality. Oral hygiene with chlorhexidine has been considered a tool in the prevention of nosocomial pneumonia. However, current data suggest that such benefits are more significant in cardiac surgeries patients. Objective: To evaluate the effects of oral chlorhexidine hygiene with tooth brushing on the rate of ventilator-associated pneumonia in a mixed population of critically ill patients under prolonged mechanical ventilation. Methods: Prospective, randomized, and placebo-controlled pilot study. Patients who were receiving mechanical ventilation, had been admitted in the intensive Care Unit in the previous 24 hours, and were anticipated to require mechanical ventilation for more than 72 hours were included in the study. The patients were randomly divided in to one of the following groups: chlorhexidine hygiene with toothbrushing or a placebo group (gel with the same color and consistency and tooth brushing). Results: The planned interim analysis was conducted using 52 patients, and the study was terminated prematurely. In total, 28 patients were included in the chlorhexidine/tooth brushing group, and 24 patients were included in the placebo/tooth brushing group. Ventilator-associated pneumonia occurred in 45.8% of the placebo group and in 64.3% of the chlorhexidine hygiene with toothbrushing group (RR=1.4; 95% CI=0.83-2.34; p=0.29). Conclusion: The use of gel with chlorhexidine 2% and toothbrushing for oral hygiene did not have effect on the rate of VAP in this heterogeneous population of critically ill patients under prolonged mechanical ventilation.